Hubungan Pengetahuan Dengan Perilaku Hidup Bersih Sehat Pada Remaja Putri - Dwi Rahayu; Ani Andriyani (coba, 2012)
Clean living healthy behaviors (PHBs) to be one government program that is expected to complete a variety of diseases and health problems. Clean and comfortable environment that will reduce negative impacts on the environment. This research design uses a Cross Sectional correlation approach. The population in this study were young women in the sixth grade girls cabin Ibtidaiyah Lirboyo as many as 62 teenagers. Studied sample of 53 adolescents using a sample random sampling technique. Independent variables in this study is the knowledge of clean healthy living, while the dependent variable is the behavior of a healthy clean life. Collecting data using questionnaires. Analyze data using Spearman Rank statistical test. The results obtained (47.17%) adolescents have adequate knowledge and category (45.28%) adolescents have poor behavior category. The results of data analysis using the Spearman Rank statistical test at α = 0.05 obtained by the correlation coefficient 010 and a significant level of 0.432. This result means that there is no relationship of knowledge about healthy living clean with a clean healthy living behaviors in adolescent girls in the sixth grade girls cabin Lirboyo Elementary. This study shows that the less knowledge about living a clean healthy then the less well their healthy hygienic behavior. This can be used as a picture or information to carry out further research related to environmental health.